MITC challenges in promoting its services via Asia Pacific incentive & meeting expo in Melbourne, Australia / Noorhidayu Musa - Musa, Noorhidayu (Faculty of Business and Management, 2010)
This project in its present form is the result analysis The Challenges MITC In Promoting Its Services Via Asia Pacific Incentive & Meeting Expo in Melbourne, Australia. The issue it was determine whether MITC have challenges to promote its services via Asia Pacific Incentive & Meeting Expo in Melbourne, Australia. MITC is the exhibition and convention centre where they participate in market their product via AIME in Melbourne. The analysis involve factor that contribute to the challenges of the promoting MITC services in Melbourne. The factors are in term of culture, technology, communication, cost and economic. AIME is Australia’s largest and most established event for people involve with the organization of meetings, conference, incentives, exhibitions, functions and product launches. The only place to discover exciting new ideas, network with the right people and lock and entire year’s events into place under one roof. The analysis shows MITC has a gap to market their services via AIME in Melbourne. The result was get from the comparison survey from the country that participate AIME. The conclusion was MITC have challenges from the aspect cost, technology and communication, knowledge of culture and stability of economic.